Synthesis and Encapsulation of Uniform Star‐Shaped Block‐Macromolecules. Issue 6 (12th October 2020) - Waibel, Kevin A.; Moatsou, Dafni; Meier, Michael A. R.
Abstract: Linear uniform oligomers synthesized via a two‐step iterative cycle are postmodified with uniform octaethylene glycol monomethyl ether and finally coupled via azide‐alkyne cycloaddition to yield uniform star‐shaped block macromolecules with a mass ranging from 10 to 14 kDa. Each of the molecules is carefully characterized by NMR, electrospray ionization mass spectrometry (ESI‐MS), and size exclusion chromatography (SEC) to underline their purity as well as their uniformity. The obtained star‐shaped macromolecules are investigated in their ability to encapsulate dye molecules by carrying out qualitative solid–liquid phase transfer experiments. Abstract : Three uniform star‐shaped block‐macromolecules (9.8–14.1 kDa) are synthesized in an iterative procedure via the arm‐first approach and carefully characterized with NMR, electrospray ionization mass spectrometry (ESI‐MS), and size exclusion chromatography (SEC) to confirm their purity. The obtained macromolecules are applied in solid–liquid phase transfer experiments to evaluate their abilities in encapsulating guest molecules.